Soil biological challenges in our age - Kátai, János (Acta Agraria Debreceniensis, 2012)
The paper deals with the soil biological research and its contribution to the changed cropping strategy and to the sustainable and environmentally friendly farming and management. The paper emphasizes the importance of biodiversity, as one of the most important ecological functions of soil. The organisms, populations and communities living in the soil play a key importance in the preservation of soil fertility. The most important research areas are presented dealing with in the last decades the national researchers and the challenges we face regarding the current soil biological problems. We have to prepare to examine the soil biological effectiveness of the more widely spread bio-preparations, bacterium preparations, and bioregulators. The prerequisites are the versatile knowledge of the biological state of soils and monitoring examination of the different effects soils had (including the mentioned preparations).